Primeros apuntes ecológicos y herpetológicos sobre el macizo del Nevado, en Mendoza - Cei, José Miguel Alfredo María (1970)
Geological and ecological aspects of an extra-andinian area corresponding to "macizo del Nevado" (Mendoza province) are described. Biogeographical and especially herpetological data of that región are reported; the most significant were those refering to the presence of Odontophrynus americanus, Bufo arenarum and mainly Bufo spinulosus, whose morphological and serological affinities with the andinian form from Mendoza are shown.